Study of entry strategy into Indochina by a Latin American market leader. - Guzman, Eugenio J. Reyes. (2009)
This study examined some of the critical factors that might influence the choice of an entry strategy into the cement market in Indochina by a Latin American market leader. The study looked at the country-specific factors, such as the existing and potential market size, the political risk of the host country, the capital controls imposed, as well as the compatibility of the culture of the host country and that of the home country of the investing company. Industry-specific factors such as the barriers to entry and the current and potential market players were also examined. The intensity of these external factors was evaluated largely based on information gathered from the cement companies and industry experts interviewed in Vietnam, Myanmar, and Laos.